2019
DOI: 10.1136/rapm-2019-100752
|View full text |Cite
|
Sign up to set email alerts
|

A review of peripheral nerve blocks for cesarean delivery analgesia

Abstract: Peripheral nerve blocks have a unique role in postcesarean delivery multimodal analgesia regimens. In this review article, options for peripheral nerve blocks for cesarean delivery analgesia will be reviewed, specifically paravertebral, transversus abdominis plane, quadratus lumborum, iliohypogastric and ilioinguinal, erector spinae, and continuous wound infiltration blocks. Anatomy, existing literature evidence, and specific areas in need of future research will be assessed. Considerations for local anestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 88 publications
2
59
0
12
Order By: Relevance
“…A meta-analysis reported that using high-dose IT morphine >100-250 mcg resulted in a range of mean times (13.8-39.5 h) to rst analgesic request. 6 In our study, the Kaplan-Meier curve showed a median pain-free period or median time to rst request for IV-PCA morphine of 2.50 h in the Group IT morphine. Similarly, a previous study at our center reported a median time to rst request for IV-PCA morphine of 2.1 h when adding IT morphine 0.2 mg. 19 There was an improvement in the pain-free period and opioid consumption during the early postoperative period when QLB was combined with IT morphine.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…A meta-analysis reported that using high-dose IT morphine >100-250 mcg resulted in a range of mean times (13.8-39.5 h) to rst analgesic request. 6 In our study, the Kaplan-Meier curve showed a median pain-free period or median time to rst request for IV-PCA morphine of 2.50 h in the Group IT morphine. Similarly, a previous study at our center reported a median time to rst request for IV-PCA morphine of 2.1 h when adding IT morphine 0.2 mg. 19 There was an improvement in the pain-free period and opioid consumption during the early postoperative period when QLB was combined with IT morphine.…”
Section: Discussionsupporting
confidence: 50%
“…[1][2][3][4] Intrathecal (IT) morphine is the standard method for postoperative pain control following spinal anesthesia for cesarean delivery 3,5 but increases the risk of maternal pruritus, nausea and vomiting and rare devastating respiratory depression. 1,[6][7] As a result of recent advances in ultrasound (US)-guided regional anesthesia, the popularity of abdominal wall block has dramatically increased during the last decade. US-guided transversus abdominis plane block (TAPB) has been shown to be an effective component of multimodal analgesia in parturients who are unable to receive neuraxial opioids or whose pain is not adequately controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary analgesic outcomes included difference in area under the curve of the weighted pooled rest pain scores at five predesignated time points (in recovery room [0 to 2 h], and at 4 to 6, 12, 24, and 48 h postoperatively); postoperative rest pain severity (VAS pain scores) in recovery room and at 4 to 6, 12, 24, and 48 h postoperatively; time to first analgesic request (hours); requirement for breakthrough analgesia in recovery room; any indicators of postoperative function and quality of recovery such as time to ambulation (hours), time to voiding (hours), time to breastfeeding (hours); patient satisfaction with pain relief; and block performance time (minutes). Secondary safety outcomes included opioid-related side effects (i.e., postoperative nausea and vomiting, excessive sedation, respiratory depression, pruritis, hypotension, and urinary retention) and block-related complications 19 (i.e., hematoma, organ injury, local anesthetic systemic toxicity, and block failure).…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%
“…A recent review of post-CD regional analgesia techniques discusses each of these approaches in detail. 2 In this issue of the Journal, Sultan et al present a network meta-analysis (NMA) comparing single-shot TAP block, single-dose wound infiltration (WI), and continuous wound catheter (WC) with a primary outcome of 24-hr opioid consumption after CD. 3 At first glance, it may be unclear from this study which technique is superior.…”
mentioning
confidence: 99%
“…Un article de revue récent s'intéressant aux techniques d'analgésie régionale postcésarienne décrit chacune de ces approches en détail. 2 Dans ce numéro du Journal, Sultan et coll. présente une méta-analyse en réseau (MAR) comparant les blocs TAP à injection unique, les infiltrations de l'incision en dose unique, et les infiltrations continues via cathéter.…”
unclassified